The Role of Compensatory Justice and Physical Work Environment in Influencing Employee Job Satisfaction - Shinta Devi Sukowati; Saiful Bahri (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
This study aims to determine the effect of compensation justice and physical work environment on the job satisfaction of employees of the Agriculture and Plantation Service of Central Java Province, Indonesia. This study uses a quantitative research approach. The population in this study amounted to 594 people and the sample studied was 86 respondents using a simple random sampling technique. The analysis tool uses statistical software with SPSS version 22. Data analysis uses multiple linear regression analysis. Partially, the compensation fairness variable has a significant effect on employee job satisfaction, as well as the physical work environment has a significant effect on employee job satisfaction. This shows that compensation fairness and physical work environment provide a positive contribution to employee job satisfaction. Further findings show that compensation fairness and physical work environment provide a high contribution to job satisfaction.